2002
DOI: 10.1016/s0035-9203(02)90074-x
|View full text |Cite
|
Sign up to set email alerts
|

A nested polymerase chain reaction (Ln-PCR) for diagnosing and monitoring Leishmania infantum infection in patients co-infected with human immunodeficiency virus

Abstract: We investigated a Leishmania-specific nested polymerase chain reaction (Ln-PCR) for the diagnosis and treatment monitoring of L. infantum infections in patients co-infected with human immunodeficiency virus (HIV). Peripheral blood and bone marrow samples from 89 HIV patients in Spain suspected of having leishmaniasis were examined by different diagnostic techniques (Ln-PCR, microscopy, NNN culture and indirect fluorescent antibody test). The sensitivity of Ln-PCR compared with microscopy and culture of bone ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
121
0
3

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 162 publications
(129 citation statements)
references
References 22 publications
5
121
0
3
Order By: Relevance
“…[21][22][23] These assays gave negative results after treatment and were unable to analyze the decrease in parasitic load during treatment. In typical cases of VL, the quantitative PCR showed that parasitemia decreases to undetectable levels between the third and the fourth administration of liposomal amphotericin B independently of the initial parasitemia.…”
Section: Discussionmentioning
confidence: 99%
“…[21][22][23] These assays gave negative results after treatment and were unable to analyze the decrease in parasitic load during treatment. In typical cases of VL, the quantitative PCR showed that parasitemia decreases to undetectable levels between the third and the fourth administration of liposomal amphotericin B independently of the initial parasitemia.…”
Section: Discussionmentioning
confidence: 99%
“…One hundred microliters of peripheral blood and 100 μL of spleen aspirate dilution were subjected to a classical phenol-chloroform DNA extraction and ethanol precipitation, and 10 μL of the extracted DNA were analyzed by PCR according to the method of Cruz and others . 25,26 Standard quality control procedures were followed. In all assays, negative controls without DNA and controls with healthy human DNA were used.…”
Section: Studymentioning
confidence: 99%
“…DNA from an estimated 10 promastigotes was used as the positive control in each experiment. 25,26 Statistical analysis. Data were entered into an Excel (Microsoft, Redmond, WA) spreadsheet and statistical analysis was performed by using Epidat version 3.1 software ( http:// www.epidata.dk/ ).…”
Section: Studymentioning
confidence: 99%
“…Estos métodos para patologías parasitarias como leishmaniasis, enfermedad del sueño, toxoplasmosis o criptosporidiasis han pasado del laboratorio de investigación a los hospitales y laboratorios de referencia basados generalmente en métodos de PCR anillada (nested PCR) para aumentar la sensibilidad del diagnóstico a partir de muestras clínicas (Cruz, et al, 2002). También se han incorporado o desarrollado métodos para la detección de marcadores de resistencia, virulencia y genotipificación molecular (Fuentes, et al, 2001).…”
Section: Introductionunclassified